Feasibility study on the use of a single digital camera for thoraco-abdominal pattern assessment - Molinaro, Nunzia; Schena, Emiliano; Bravi, Marco; Miccinilli, Sandra; Sterzi, Silvia; Silvestri, Sergio; Massaroni, Carlo (2023 IEEE International Workshop on Metrology for Industry 4.0 & IoT (MetroInd4.0&IoT), 2023)
Contactless technologies are gaining interest as promising systems for the remote monitoring of parameters of physiological interest without interfering with the subject's comfort. Among the existing technologies, digital cameras integrated into smartphones are widely used due to their ease of use, unobtrusiveness, availability. In this study, we investigated the potentiality of using a smartphone's built-in camera for the assessment of thoraco-abdominal movements without the need of use any markers on the torso. Besides the estimation of respiratory rate f R ), we carried out an explorative analysis of thoraco-abdominal asynchronies by computing the phase shift between the thoracic and abdominal traces. Data were recorded from three healthy volunteers and one patient with respiratory disorders. A Motion Capture System (MoCap) was used as a reference to acquire the thoracic and abdominal respiratory patterns. Results show a good accordance between the thoracic and abdominal respiratory waveforms extracted from the video and those of the MoCap. In addition, a good agreement was achieved in the estimation of f R (MOD close to 0 bpm and LOAs between ± 0.26 bpm and ± 1.63 bpm).